SIMILE IN AT FIRST SIGHT NICHOLAS SPARKS’S NOVEL - Elsabat Lumbantoruan; Sumarsih (State University of Medan, 2015)
This study is concerned with simile in At First Sight novel. This study wasconducted by using descriptive qualitative design as the research method. Theobjectives of this study were to find out the types of simile used based on Hassanand Halliday’s theory and the reason for using simile in At First Sight novel. Thedata of this research were 272 sentences signed with simile that occured in AtFirst Sight novel. The research findings were four types of simile, they were“like” (119), “as if” (69), “as” (66), “as...as” (18), and five reasons were: toenhance all words by adding portrayal and original, to offer personal experienceand emotional hook, to make the sentences more creatively and shorter, to addgreat depth and imagery, and to create a powerful mental pictures